PENGARUH KEMUDAHAN DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN PENGGUNA JASA GO-JEK DI BANDAR LAMPUNG - Viola De Yusa; Ana Risqa JL (Program Pascasarjana Universitas Gajayana, 2018)
Go-Jek is a transportation company based on e-business applications. The presence of onlineapplication-based transport services that use the internet is very influential for the communityin all activities quickly and efficiently. Go-Jek has provided some convenience for theconsumer. So far, consumers who want to order one must wait for the roadside or walk tothe motorbike base. With the application Go-Jek then consumers can message anywhere hewas good at home, street and so forth. Consumer confidence in the services provided byGo-Jek will create issues or rumors that circulate quickly, not only in cyberspace but in thereal world, and this will make people aware of the existence of mockups. This study aims todetermine the level of satisfaction in using services Go-Jek. The population in the study wereconsumers of service users of Go-Jek with a sample of 100 respondents. Descriptive researchmethod with multiple linear regression analysis tools. Based on the result of research andhypothesis of easiness and trust variable have an effect on to customer satisfaction ofservice user of Go-Jek in Bandar Lampung.